ON THE JOURNALISTIC WORK OF SADRIDDIN AYNI CONCERNING ISSUES OF BUKHARA HISTORY - Farrux Umedovich, Temirov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigates the journalistic contributions of Sadriddin Ayni between 1920 and 1923 to reveal their significance in documenting Bukhara’s socio-political transformations and preserving its cultural heritage. Method: A qualitative content analysis was conducted on several lesser-known articles by Ayni, including “Let Them See and Hear,” “Address to the Jadids and Revolutionaries of Bukhara,” and “Mir Arab Buildings,” which were not included in his official collected works. Results: The findings demonstrate Ayni’s active engagement in chronicling the Soviet restoration of Bukhara, advocating for the humane treatment of the Emir’s relatives, and emphasizing the importance of cultural preservation. His collaboration with local intellectuals and support for historical societies illustrate his dual function as both a journalist and historian. Novelty: This study highlights rare and previously overlooked journalistic writings of Ayni, offering new perspectives on his role in Central Asian historiography and intellectual activism, thus contributing original insight into the historiographical narratives of early 20th-century Bukhara.